ANALISIS GAYA BELAJAR SISWA SD NEGERI 006 TANJUNG MEDAN - Mardiana '; Rosmawati '; Abu Asyari Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstrackThis study entitled"Analysis of Elementary SchoolStudents' LearningStyles006TanjungMedan". This studyaims to determine thestudent's learning styleElementary School006TanjungMedan, be itlearning stylevisual, auditoryNorKinesthetic. The formulation of theproblemin this studyis: HowVisuallearningstylepictureelementary schoolstudents006TanjungMedan, HowlearningstylepictureAudentik006elementary schoolstudentsTanjungMedan, as well asan overviewHowPsychomotorlearningstylesof studentsof SD Negeri006TanjungMedan?. Fromthe formulation ofthe problem canbe seenthatthe purposeof thisstudyis: Todeterminethe student's learning style VisualElementary School006TanjungMedan, To know theauditorylearning style006elementary schoolstudentsTanjungMedan, andto knowKinestheticlearningstylesof studentsof SD Negeri006TanjungMedanmethodusedinthisresearchisdescriptive method, analytic. Andthe data processedin this studyis dataaboutstudent learningstylesinprimary school006TanjungMedan. And thepopulationin this study wereallstudents of classIV, V, andVIElementary School006TanjungMedan. Data collection toolwas aquestionnaire, which isaboutempathyquestionnaireconsistingof20questions. Keywords: Elementary SchoolStudents' LearningStylesN006TanjungMedan